Sediment Balance in the Blue Nile in Sudan - A. Gismalla, Younis (Gezira Journal of Engineering and Applied Sciences; Vol 9 No 2 (2014), 2018)
The Blue Nile is one of the two main tributaries of the Nile River. It originates in the Ethiopian Plateau. The Blue Nile water plays an important role in the economic development of Sudan in terms of irrigated agricultural development and hydropower generation. The average annual flow of the Blue Nile is 50 billion cubic meters, 80% of it occurs during the flood season (July – October). During the flood season the river brings down large amounts of sediment estimated as 146 million tons per year. The sediment material originates mainly from heavy erosion in the upper catchment area in Ethiopia. The Blue Nile system within Sudan includes two reservoirs, Roseires and Sennar, and two tributaries, viz. Dinder and Rahad. Sennar and Roseires reservoirs have already lost 65% and 34% of their initial storage capacities due to sedimentation, respectively. The Blue Nile sediment in Sudan is monitored at a number of stations scattered along its length. The sediment concentrations vary during the flood season and from year to year. The sediment load is also variable along the river length due to deposition in the river channel, trapping in the reservoirs, diversion to irrigated schemes and inputs from tributaries. In this paper the sediment trap efficiency of each reservoir is calculated using bathymetric survey data. The current trap efficiency of Roseires and Sennar reservoirs is found to be 17% and 5%, respectively. The average annual sediment diverted to Gezira Scheme is 8.5x10 6 tons. The spatial sediment distribution along the Blue Nile is given at key river nodes. Upstream and downstream each reservoir and at Gezira canals’ off-takes and at its confluence with the White Nile. The annual average sediment contribution of the Blue Nile to the Main Nile is found to be 143x10 6 tons. The paper also reviews the main characteristics of the Blue Nile sediment that affect its transport and deposition.